The impact of the COVID pandemic on primary care diabetes services in the UK: A cross-sectional national survey of views of health professionals delivering diabetes care. Issue 2 (April 2022) - Seidu, Samuel; Hambling, Clare; Holmes, Patrick; Fernando, Kevin; Campbell, Nigel S.; Davies, Sarah; Khunti, Kamlesh; ,
Highlights: Primary care is now overworked and emotionally drained due to the pandemic. Concerns about infecting a family member is associated with emotionally drain. Telephone was the most common consultation type used to provide diabetes care. The COVID-19 pandemic impact on their practice's ability to provide routine diabetes care. Screening for type 2 diabetes was reported to have been impacted on by 70.6% of people. Abstract: Background: Healthcare systems worldwide have been adversely affected by the Coronavirus disease 2019 (COVID-19) pandemic. There has been a substantial decrease in admissions for acute medical conditions with longer delays between the onset of the symptoms and hospital treatment compared to the pre-pandemic period. The impact of the COVID pandemic on primary care services is uncertain. Aim: Using an online survey, we examined the impact of the COVID pandemic on primary care diabetes services in the UK. Methods: An online survey was developed by the Primary Care Diabetes Society research group and administered to healthcare and allied health professionals delivering diabetes care in the UK from January to May 2021. Descriptive statistics and odds ratios (ORs) with 95% confidence intervals (CIs) were estimated. Results: Of the 1070 professionals surveyed, 975 (91.1%) completed the questionnaire. Most respondents were nurses or nurse practitioners (59.7%) and doctors (32.9%). The mean age of respondents was 52 years and 79% were female. The majority of respondents felt overloaded with work (71.2%) or emotionally drained at the end of a working day (79.1%) compared with the pre-pandemic period. Being a doctor and worried about infecting a family member with the Coronavirus were each associated with an increased odds of being substantially overworked or emotionally drained: (OR = 2.52; 95% CI, 1.25−5.07) and (OR = 2.05; 95% CI, 1.24–3.39), respectively. The most common consultation method used to provide diabetes care during the pandemic was telephone consultation (92.0%). Overall 79.1% of respondents felt the COVID-19 pandemic had had moderate to significant impact on their practice's ability to provide routine diabetes care; 70.6% of respondents felt the COVID-19 pandemic had had moderate to significant impact on their practice's ability to provide routine health checks or screening for type 2 diabetes and approximately half of respondents (48.3%) reported encountering mental health concerns in people with diabetes. Conclusions: COVID-19 pandemic has had significant impact on the ability of healthcare professionals and their practices to deliver routine diabetes care. Failure to restore primary care provision urgently and safely to at least pre-pandemic levels in a sustainable manner may lead to emotionally drained and overworked workforce in primary care, place additional burden on the already overburdened healthcare system and worse outcomes for patients.